Convergence of Martingales in Orlicz–Kantorovich Lattice - Ganiev, Inomjon (Institute for Mathematical Research (INSPEM) Universiti Putra Malaysia, 2016)
In the present paper we prove convergence of martingales in OrliczKantorovich lattices. Our main tool is the use of methods of measurable bundles of Banach-Kantorovich lattices.